Perkembangan Kebudayaan Masyarakat Kerinci Masa Kolonial (1904-1906) - Yana Safitri; Pipi Emi Julianti; Junita Yosephine Sinurat (Prabayaksa: Journal of History Education, 2024)
Kerinci society before the emergence of the Dutch had two patterns of government, namely conservative and ulama, the region had an important role in Kerinci society in determining and implementing existing regulations. The emergence of Kekerinci expansionism is considered to be detrimental to the plans and demands of the community, so that indigenous people and ulama oppose regional development with different structures and examples of obstacles. Kerinci culture is the work of the Kerinci people. The historical background of improvements is widely known at the public and global levels and is a significant source of values, motivation and reasons for understanding public activities, which must be realized in the improvement cycle carried out by regional legislatures, especially the Kerinci region. The Government and Sungaifull Regional Government are the institutions that oversee the Kerinci Regular Smoothness organization. This article will discuss the social development of Kerinci society during the border period (1904-1906). The strategy used in the hard copy form of this article is an interesting subjective exploration technique with a concentration approach to writing.